[38] Efficacy of silodosin on the outcome of semi-rigid ureteroscopy for management of large distal ureteric calculi: single-blinded placebo-controlled randomised trial - Yasser Noureldin (Taylor & Francis Group, 2018)
Objective: To evaluate the efficacy of administration of silodosin, as a new α-adrenergic blocker (AAB), on the success rate of semi-rigid ureteroscopy (URS) for the management of large distal ureteric stones. Methods: This prospective study recruited 127 adult patients with single distal ureteric stones of ⩾1 cm. Patients were randomly allocated to two groups. The first group included 62 patients who received silodosin (8 mg) for 10 days before URS (Silodosin Group), whilst the second group included 65 patients who received placebo in the form of multivitamins for 10 days before URS (Placebo Group). All patients underwent URS and a pneumatic lithoclast was used. Results: The mean operative time was shorter in the Silodosin Group than in the Placebo Group, at a mean (SD) of 41.61 (4.67) vs 46.85 (4.6) min, respectively. Furthermore, forwarding the ureteroscope to access the stone failed in a statistically significant number of patients in the Placebo Group compared with the Silodosin Group (13 vs two cases, respectively). The complication rate was significantly higher in the Placebo Group compared with the Silodosin Group (20% vs 6.4%, P = 0.036). Moreover, the need for postoperative analgesia was significantly lower in the Silodosin Group compared with the Placebo Group (8.1% vs 26.2%, P = 0.009). Conclusion: Silodosin intake before ureteroscopic management of large distal ureteric stones seems to be associated with better ureteroscope forwarding to access the stones, shorter procedural time, higher stone-free rate, lower incidence of complications, and lower need for postoperative analgesia.